Shelf-life Evaluation of Mango Jelly Candy: Critical Moisture Content Method - Yudiastuti, Silvia Oktavia Nur; Handayani , Wiwik; Halim , Abdul; Putri, Aurelia Rosa Azaria (Sebatik, 2025)
Using the critical moisture content method, this study investigated the shelf life of mango jelly candy made from over-ripe arum manis mango. The product's shelf life must be evaluated to determine its effect after combining with citric acid. Tests were conducted using 0.5%, 1%, and 1.5% concentrations of citric acid. The mango jelly was wrapped in polypropylene packaging at a relative humidity (RH) of 78% and a temperature of 290 °C. Based on the analysis results, adding 0.5% citric acid yields a product with a longer shelf life compared to concentrations of 1% and 1.5%. An increase in the pH of mango jelly candy causes this. An increase in pH can cause syneresis, thereby increasing the water content in the jelly, which ultimately increases the Aw, allowing it to become a growth medium for microorganisms and resulting in a decrease in the characteristics of the mango jelly candy. The characteristics of the mango jelly product at a concentration of 0.5% as the chosen product formulation concentration are water content 19.91%, ash content 1.3%, fat content 0.33%, protein content 0.71%, and carbohydrate content 77.77%, and IC50 value at 16.11, with hedonic test values ​​for aroma at 3.56, color at 4.04, taste at 4.0, and texture at 3.56. All stored products, whether treated as A1, A2, or A3, will be damaged on the 4th day of storage. Based on Labudza's calculation analysis, mango jelly candies A1, A2, and A3 have shelf lives of 12, 8, and 6 days, respectively. And three days.